INTENSIFICATION OF LUXURY BRAND VALUE - A SYSTEMATIC LITERATURE REVIEW - Kataria, Shifali; Singla, Deepika (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Purpose: The current study intends to delve into the aspects that increase the overall luxury value of premium products exposing the consumer behaviour while attaining the final purchase decision. Design/methodology/approach: The study aims to provide a systematic review of the extant scholarly literature in the area. An extensive assessment of literature has been done on 111 English language articles that were well searched for on a leading database. The researchers provide detailed profiling and thematic analysis through comprehensive content analysis. Findings: Key research gaps and future research questions along with a unified framework of the complete literature review are postulated. The increase of overall luxury value leads to an upsurge in the final purchase of luxury products which is centred around few major dimensions. However, there is a lack of research over the financial aspects of consumers for luxury brand consumption which needs to be explored further. Originality: The current review study contributes to an increasing interest in luxury value dimensions, ultimately increasing the demand for luxury brands. The article highlights the future research avenues in this area supported by appropriate data.